Rheological and biological properties of a hydrogel support for cells intended for intervertebral disc repair - Benz, Karin; Steck, Eric (BMC musculoskeletal disorders, 2012)
Cell-based approaches towards restoration of prolapsed or degenerated intervertebral discs are hampered by a lack of measures for safe administration and placement of cell suspensions within a treated disc. In order to overcome these risks, a serum albumin-based hydrogel has been developed that polymerizes after injection and anchors the administered cell suspension within the tissue.
Gesehen am 17.04.2018